Lignin-based Pickering emulsion and preparation method thereof

By dissolving lignin in a low-eutectic solvent and combining with sodium alginate, the problems of unevenness and dispersion of lignin in Pickering emulsion are solved, and a high stability and oxidation resistance of wood is achieved. The min-based Pickering emulsion has expanded its application prospects in biomedical and anti-photolytic drugs.

CN119431823AActive Publication Date: 2025-02-14CHINA PHARM UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411568136.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

When using lignin-stabilized Pickering emulsion in the prior art, there are problems such as high unevenness, poor dispersion, large particle size and poor UV resistance, which limits its application in biomedical and anti-photolysis drugs.

Method used

Lignin-based Pickering emulsion was prepared by dissolving lignin in a low eutectic solvent and combining with sodium alginate.

Benefits of technology

High-performance preparation of lignin nanoparticles is achieved, the stability and dispersion of the emulsion are improved, and the in vitro antioxidant and biocompatible of hydrophobic biological active ingredients are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431823A_ABST
    Figure CN119431823A_ABST
Patent Text Reader

Abstract

The invention discloses a lignin-based Pickering emulsion and a preparation method thereof, and belongs to the technical field of biochemistry. The preparation method comprises the following steps: dissolving lignin in a deep eutectic solvent, diluting, dialyzing and freeze-drying to obtain lignin nanoparticles, dissolving the lignin nanoparticles and sodium alginate in a water phase, mixing the water phase and an oil phase, and homogenizing at ultrahigh pressure to obtain the lignin-based Pickering emulsion. After the concentration (7.5 mg / mL) of the lignin dissolved in the eutectic solvent is adjusted, the particle characteristics of the prepared nanoparticles are obviously improved, and the nanoparticles are more suitable for being used as an emulsion stabilizer; the stability of the emulsion is further improved by further optimizing the concentration of lignin nanoparticles (1wt%) and sodium alginate (0.9 wt%) in the water phase; hydrophobic bioactive components (such as curcumin) are loaded in the emulsion prepared by the invention, so that the antioxidant activity and biocompatibility of the active components can be further improved; the emulsion has wide application prospects in the fields of biological medicine, cosmetics, food industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biochemistry, and in particular to a lignin-based Pickering emulsion and a preparation method thereof. Background Art

[0002] Pickering emulsions are solid particle-stabilized emulsions, which consist of an aqueous phase, an oil phase, and solid particles. The solid particles are adsorbed to the interface between the two phases to prevent the droplets from coalescing, thereby stabilizing the emulsion. Generally, hydrophilic solid particles can stabilize water-in-oil emulsions, and hydrophobic solid particles can stabilize oil-in-water emulsions. Compared with traditional surfactant-stabilized emulsions, Pickering emulsions have the advantages of high stability, low toxicity, good biocompatibility, and environmental friendliness. They have been widely used in the fields of drug delivery, cosmetics, and food industry. There are many solid particles used to stabilize Pickering emulsions, which are mainly divided into inorganic particles and organic particles. Considering the limitations of their own toxicity, biodegradability, and compatibility, many particles are not suitable as stabilizers for Pickering emulsions used in the biomedical field.

[0003] Lignin is one of the three main components of lignocellulosic biomass and is the second largest renewable resource after cellulose. Lignin is the only natural aromatic raw material that can be extracted in large quantities from terrestrial plants. It has the advantages of abundant sources, easy access, and environmental friendliness, and has great potential in the preparation of high-value chemicals and advanced materials. Lignin is a natural polyaromatic macromolecular compound composed of hydrophobic non-polar groups with phenylpropane as the skeleton and hydrophilic polar groups such as carboxyl and hydroxyl. It has good surface activity, such as amphiphilicity and antioxidant properties, through modification. However, the high heterogeneity, poor dispersibility, and large particle size of lignin are the main factors limiting the stabilization of lignin Pickering emulsions. In addition, the UV resistance of lignin itself is not ideal, which seriously hinders the application of lignin-based Pickering emulsions in anti-photolysis drugs.

[0004] Relevant studies have shown that lignin nanoparticles can overcome the shortcomings of natural lignin and use them as stabilizers for Pickering emulsions, which can achieve high added value of lignin. However, current research on Pickering emulsion drug delivery mainly focuses on increasing the thickness of the wall material to solve problems such as poor emulsion stability and easy demulsification. For example, the stability of the Pickering emulsion can be increased by adding a cross-linking agent to induce a cross-linking reaction at the emulsion interface; and in order to further increase the density of the capsule wall to delay drug release, technicians in this field also choose to aminize lignin to strengthen the reaction between lignin and the cross-linking agent to increase the thickness of the wall material.

[0005] Although the above method can effectively release the target drug, it inevitably uses non-environmentally friendly toxic reagents, such as formaldehyde, tetrahydrofuran, etc. Therefore, it is of great significance to find a safe and green alternative for preparing lignin-based Pickering emulsions. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art and provide a lignin-based Pickering emulsion and a preparation method thereof. The preparation process is simple, safe and efficient. The prepared emulsion has the characteristics of high stability and storage resistance, and can significantly improve the in vitro antioxidant and biocompatibility of hydrophobic bioactive ingredients (such as curcumin). The emulsion has broad application prospects and promotion value.

[0007] In order to achieve the above technical objectives, the present invention is implemented by the following technical scheme: a method for preparing a lignin-based Pickering emulsion, comprising the following steps:

[0008] 1) preparing a low eutectic solvent, adding water, cooling and setting aside;

[0009] 2) dissolving lignin in a low eutectic solvent, standing, and centrifuging to obtain a lignin solution;

[0010] 3) diluting the lignin solution dropwise with deionized water, dialyzing, and freeze-drying to obtain lignin nanoparticles;

[0011] 4) dissolving lignin nanoparticles and sodium alginate in an aqueous phase, mixing the aqueous phase and the oil phase, and homogenizing under ultrahigh pressure to obtain a lignin-based Pickering emulsion.

[0012] Furthermore, in step 1), the preparation method of the low eutectic solvent is: betaine and lactic acid are mixed in a molar ratio of 1:1.5 to 2.5, and heated in a water bath at 80 to 95° C. until they are completely dissolved, thereby forming a low eutectic solvent.

[0013] Furthermore, in step 2), the dissolution process is carried out at 20-30° C., the dissolution process is assisted by magnetic stirring, the stirring speed is 600-800 rpm, the standing time is 10-14 hours, and the concentration of lignin in the obtained lignin solution is 7-10 mg / mL.

[0014] Preferably, the concentration of lignin in the obtained lignin solution is 7.5 mg / mL.

[0015] Furthermore, in step 3), the dilution process is assisted by magnetic stirring, the stirring speed is 600-800 rpm, the dropping rate of deionized water is 1 mL / min, and the final weight percentage of the added deionized water is 50 wt%.

[0016] Furthermore, in step 4), the weight percentage of the lignin nanoparticles in the aqueous phase is 0.5-1 wt%, and the weight percentage of the sodium alginate is 0.6-0.9 wt%.

[0017] Preferably, the weight percentage of lignin nanoparticles in the water phase is 1 wt %, and the weight percentage of sodium alginate is 0.9 wt %.

[0018] Furthermore, in step 4), the volume ratio of the oil phase to the water phase is 1:9 to 9:1, preferably 3:7.

[0019] Furthermore, the oil phase is one of rapeseed oil, soybean oil, olive oil and linseed oil.

[0020] The lignin-based Pickering emulsion prepared by the above method exhibits good storage resistance and moderate dispersion stability. Curcumin is loaded in the emulsion, and the emulsion exhibits good in vitro antioxidant properties and biocompatibility.

[0021] The beneficial effects of the present invention are:

[0022] 1. In the present application, lignin is dissolved in a low eutectic solvent and the concentration of lignin is adjusted to prepare high-performance lignin nanoparticles. Compared with untreated lignin, the particle size of the nanoparticles is increased, the dispersibility is optimized, the Zeta potential value is increased, there is a stronger π-π interaction inside the particles, and the particles are partially hydrophobic. These changes in particle properties enable the nanoparticles to better bind to the droplet surface, are more stable at the water-oil interface, and are more suitable as emulsion stabilizers;

[0023] 2. In addition to adding lignin nanoparticles to the aqueous phase, the present application also adds a certain amount of sodium alginate, and improves the stability of the emulsion by adjusting the amount of sodium alginate added. When the amount of sodium alginate added to the emulsion is 0.9wt%, the stability of the emulsion is significantly improved;

[0024] 3. The lignin-based Pickering emulsion prepared in the present application is an oil-in-water Pickering emulsion. By adjusting the concentrations of lignin nanoparticles (1 wt %) and sodium alginate (0.9 wt %) in the aqueous phase, the prepared emulsion exhibits good storage resistance and dispersion stability;

[0025] 4. The hydrophobic bioactive ingredient curcumin was loaded into the lignin-based Pickering emulsion prepared in the present application, and the curcumin-loaded emulsion showed better biocompatibility and in vitro antioxidant properties;

[0026] 5. The preparation scheme of the lignin-based Pickering emulsion disclosed in the present application is simple and efficient. The main raw materials, lignin and sodium alginate, are easy to obtain and have abundant sources. The preparation conditions are mild and no non-environmentally friendly reagents are required. It is a safe and green Pickering emulsion preparation process and has broad application prospects in the fields of biomedicine, cosmetics and food industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a flow chart of preparing the lignin-based Pickering emulsion in Example 1;

[0028] Figure 2 The particle size distribution diagram (A) and potential diagram (B) of different lignin nanoparticles prepared in Example 1;

[0029] Figure 3 Fourier transform infrared spectra of different lignin nanoparticles prepared in Example 1;

[0030] Figure 4 This is a contact angle measurement diagram of different lignin nanoparticles prepared in Example 1;

[0031] Figure 5 Scanning electron microscope images of different lignin nanoparticles prepared in Example 1;

[0032] Figure 6 The graphs are statistical graphs of the chromatography coefficients of different lignin-based Pickering emulsions, where panel A reflects the effect of different amounts of lignin nanoparticles added to the water phase on the emulsion chromatography coefficient, and panel B reflects the effect of different amounts of sodium alginate added to the water phase on the emulsion chromatography coefficient;

[0033] Figure 7 Microscopic images of different lignin-based Pickering emulsions;

[0034] Figure 8 The in vitro antioxidant test results of the lignin-based Pickering emulsion loaded with curcumin, wherein panel A is the test result of the DPPH·free radical scavenging experiment, and panel B is the test result of the ABTS+·free radical scavenging experiment;

[0035] Fig. 9 The results of the cell activity experiment of lignin-based Pickering emulsion loaded with curcumin. DETAILED DESCRIPTION

[0036] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0037] Experimental materials: Lignin (de-alkalized) was purchased from Maclean (purity 90%, Shanghai, China), sodium alginate was purchased from Aladdin (AR, Shanghai, China), and curcumin was purchased from Maclean (purity 98%, Shanghai, China).

[0038] Example 1

[0039] This example discloses a method for preparing a lignin-based oil-in-water Pickering emulsion. Figure 1 , the specific steps are as follows:

[0040] 1) betaine (BE) and lactic acid (LA) are mixed in a molar ratio of 1:2, heated in a water bath at 90° C. and stirred until completely dissolved to form a deep eutectic solvent (DES), 30 wt % of deionized water is added, and the mixture is cooled at room temperature for later use;

[0041] 2) At 25°C, with magnetic stirring at 600 rpm, different amounts of lignin were dissolved in DES to prepare lignin solutions with lignin concentrations of 5, 7.5, and 10 mg / mL, and the solutions were allowed to stand for 12 h to completely dissolve the lignin, and insoluble impurities were removed by centrifugation at 5000 × g for 10 min;

[0042] 3) using a constant flow pump to dilute the lignin solution dropwise with deionized water at a rate of 1 mL / min, the dilution process was assisted by magnetic stirring (600 rpm), the final weight percentage of deionized water was 50 wt%, and the obtained colloidal suspension was treated with a dialysis bag with a molecular weight cutoff of 8-14 kDa for 72 h, and freeze-dried to obtain lignin nanoparticles (LNP). The nanoparticles prepared based on lignin solutions with concentrations of 5, 7.5, and 10 mg / mL were correspondingly recorded as LNP-5, LNP-7.5, and LNP-10;

[0043] 4) Disperse different lignin nanoparticles in water, mix different lignin dispersions with sodium alginate aqueous solution in a volume ratio of 1:1 to form an aqueous phase, wherein the weight percentage of lignin nanoparticles in the aqueous phase is 1wt%, the weight percentage of sodium alginate is 0.9wt%, and rapeseed oil is added as the oil phase, and the oil-water ratio is 3:7. Use an ultra-high pressure homogenizer (SCIENTZ-207A, Xinzhi, Ningbo, China) to prepare the emulsion under a homogenization pressure of 80Mpa, and the preparation process is repeated 15 times. The emulsions prepared based on LNP-5, LNP-7.5 and LNP-10 are respectively recorded as LPE-5, LPE-7.5 and LPE-10.

[0044] Related performance testing

[0045] 1. Particle size and potential test of nanoparticles LNP-5, LNP-7.5 and LNP-10

[0046] 1) The average particle size and particle size distribution of lignin nanoparticles were determined by DLS measurement at 25°C using a particle size analyzer (ZetasizerNano-ZS, Malvern Instruments, UK). The weight percentage of solid particles in all suspensions was 0.5 wt% and diluted 10 times with deionized water. The test results are shown in Figure 2 As shown in the middle panel A, the size of the prepared nanoparticles increases significantly with the increase of lignin concentration in DES. However, although LNP-10 has the largest average particle size of 242.1 nm, LNP-7.5 has the largest PDI of 0.265, indicating that LNP-7.5 is relatively evenly dispersed in water, which is conducive to emulsification.

[0047] 2) Zeta potential indicates the surface charge of the nanoparticles, and Zeta potential affects the stability of the emulsion. Zeta potentials with positive potentials greater than +30mV or negative potentials greater than -30mV are generally considered stable. Particle size may be a factor that affects the zeta potential. The specific surface area increases with increasing particle size, and there are phenolic hydroxyl and carboxyl groups on the surface of LNP, both of which are negatively charged. High Zeta potential values ​​(positive or negative) also indicate that there is sufficient double-layer electrical repulsion between nanoparticles, which can prevent them from aggregating, which means that higher potential values ​​are beneficial to the stability of the emulsion. Figure 2 As shown in panel B, the Zeta potential value of the prepared LNP increases with the increase of lignin concentration in DES.

[0048] 2. Fourier infrared spectroscopy

[0049] The interactions between the various components in the Pickering emulsifier were investigated using Fourier transform infrared spectroscopy (TENSOR27, Bruker Corporation, Germany). Freeze-dried LNP-5, LNP-7.5, and LNP-10 samples were mixed with KBr at a mass ratio of 1:100 (w / w). The spectra of the samples were recorded between 4000 and 400 cm -1 The wave number range is 4 cm with a resolution of -1 . See Figure 3 , the characteristic absorption band of untreated lignin was identified as 3347.9 cm -1 (OH stretching of aliphatic and phenolic parts), 2937.1 cm -1 and 2853.1cm -1 (CH stretching of methyl and methylene), 1715.6cm -1 (OH deformation in phenol), 1263.7cm -1 (CO stretching in guaiacol unit), 1209.1 cm -1(CO stretch of phenol), 1139.7cm -1 (CO and CC variations of guaiacol units) and 1038.2 cm -1 (aromatic CH deformation of guaiacol units). The spectrum of LNPs contains all characteristic absorption bands of aromatic structures, phenolic groups, and guaiacol units (G), indicating that the treatment of lignin with DES has no destructive effect on the internal structure compared to untreated lignin. However, the intensity of these characteristic signals is lower in LNPs, indicating that a higher content of lignin fragments is produced. For LNP-7.5, the two peaks related to the vibration of the lignin aromatic skeleton are from 1513.2 cm -1 and 1427.1cm -1 Move down to 1511.3cm -1 and 1424.6cm -1 It reveals that there are stronger π-π interactions in LNP-7.5 than in the lignin raw material.

[0050] 3. Measuring the contact angle of different lignin nanoparticles

[0051] The three-phase contact angle (θ) of solid nanoparticles at the oil-water interface is an important factor in determining the stability of Pickering emulsions. When θ>90°, the particles are mainly located in the oil phase, and when θ<90°, the particles are mainly located in the water phase. Generally speaking, particles at the oil-water interface should have appropriate wettability; particles that are too hydrophilic or hydrophobic cannot form stable emulsions.

[0052] Figure 4 The contact angles of lignin raw material, LNP-5, LNP-7.5 and LNP-10 are shown. From the figure, it can be seen that the hydrophilicity of LNP-5 is comparable to that of untreated lignin, and the contact angle is low. The particles will be mostly wetted by the droplets, and it is difficult to prevent the droplets from agglomerating. However, the contact angles of LNP-7.5 and LNP-10 increase, and they are partially hydrophobic, can be wetted by both liquids, and better bind to the droplet surface, making them more suitable as stabilizers.

[0053] 4. Scanning electron microscope images of different lignin nanoparticles

[0054] The microstructure of all LNPs was observed by scanning electron microscopy images. All samples were dried on glass substrates and sprayed with a thin layer of gold to prevent charging effects on the samples. Scanning electron microscopy images of lignin (untreated), LNP-5, LNP-7.5, and LNP-10 are shown in Figure 5, it is observed that the morphology of LNP-7.5 is mostly spherical, with a smooth surface and no pores. Observing the image of LNP-5, it can be seen that it is a spherical and quasi-spherical shape full of pores, such as a double-sided concave disk shape and other irregular shapes. This may be because the lower the lignin concentration, the more the solvent evaporates, resulting in lower pressure inside the particles, causing collapse. As the lignin concentration increases, the lignin solution becomes thicker and more viscous, resulting in a high possibility of droplet expansion, and the nanoparticles become larger and rounder.

[0055] 5. Determination of the chromatography coefficient of lignin-based Pickering emulsion

[0056] Based on the excellent particle characteristics of LNP-7.5, the chromatography coefficient test was carried out using LNP-7.5.

[0057] 1) Effect of different concentrations of lignin nanoparticles in the aqueous phase on the emulsion chromatography coefficient

[0058] The lignin nanoparticles LNP-7.5 were dispersed in water at different weight percentages, and different lignin dispersions were mixed with sodium alginate aqueous solution at a volume ratio of 1:1 to form an aqueous phase, and the final weight percentages of LNP-7.5 in the aqueous phase were 0.25wt%, 0.5wt%, 0.75wt% and 1wt%, respectively, and the weight percentage of sodium alginate in the aqueous phase was 0.9wt%; rapeseed oil was added to the dispersed phase, and the oil-water ratio was 3:7. The emulsion was prepared using an ultra-high pressure homogenizer (SCIENTZ-207A, Xinzhi, Ningbo, China) at a homogenization pressure of 80Mpa, and the preparation process was repeated 15 times.

[0059] The chromatographic coefficient value is used to characterize the anti-stratification stability of the emulsion. The same volume of emulsion is placed in a glass bottle, and the total height (HE) and the height of the clear liquid layer (HS) of the sample are measured at the designed time point.

[0060]

[0061] Results Figure 6In the middle panel A, to some extent, the effect of changes in the concentration of lignin nanoparticles on the emulsion is similar to that of surfactants. As the concentration of LNP-7.5 in the aqueous phase increases to 1wt%, more nanoparticles gather at the oil-water interface to form droplets with smaller particle sizes. However, when the concentration of LNP-7.5 particles continues to increase, the adsorption of particles at the interface does not increase significantly. Too many nanoparticles will enter the continuous phase, making the viscosity of the emulsion too high and the droplet dispersion effect poor. On the other hand, micelles will be formed in the continuous phase, producing an Ostwald ripening effect, causing small droplets to gradually dissolve and large droplets to grow, the average particle size of the system to increase, and the aggregation rate of droplets to increase. Considering the effects of different concentrations on the stability of the emulsion, the emulsion prepared with an aqueous phase containing 1wt% lignin nanoparticles LNP-7.5 has better stability.

[0062] 2) Effect of different sodium alginate concentrations in the aqueous phase on the emulsion chromatography coefficient

[0063] The lignin nanoparticles LNP-7.5 were dispersed in continuous phase water, and the lignin dispersion was mixed with sodium alginate aqueous solutions of different mass percentage concentrations at a volume ratio of 1:1 to form different aqueous phases, wherein the mass percentage of LNP-7.5 in the different aqueous phases was 1wt%, and the mass percentages of sodium alginate in the different aqueous phases were 0wt%, 0.3wt%, 0.6wt%, and 0.9wt%, respectively. Rapeseed oil dispersed phase was added to the aqueous phase with an oil-water ratio of 3:7, and an emulsion was prepared using an ultra-high pressure homogenizer (SCIENTZ-207A, Xinzhi, Ningbo, China) at a homogenization pressure of 80 MPa.

[0064] High molecular weight polymers are usually used as thickeners to increase the viscosity of the continuous phase of the emulsion, and can also strengthen the phase interface of the emulsion and increase the stability of the emulsion. In this application, sodium alginate is added to the aqueous phase of the emulsion to change the stability of the emulsion. The effect of sodium alginate concentration on the anti-stratification stability of the emulsion is observed by adjusting the amount of sodium alginate added. The results are shown in Figure 6 In the middle panel B, the experimental results show that the addition of sodium alginate significantly enhances the anti-stratification stability of the emulsion. When the addition amount of sodium alginate in the aqueous phase is 0.9wt%, the chromatographic coefficient of the emulsion decreases significantly with the extension of storage time. However, if the concentration of sodium alginate in the aqueous phase is further increased, there will be obvious agglomeration, so the optimal addition amount of sodium alginate is 0.9wt%.

[0065] 6. Microscopic image of lignin-based Pickering emulsion

[0066] Untreated lignin, LNP-5, LNP-7.5 and LNP-10 were dispersed in water respectively, and the lignin dispersion was mixed with an aqueous sodium alginate solution at a volume ratio of 1:1 to form an aqueous phase, wherein the weight percentages of untreated lignin, LNP-5, LNP-7.5 and LNP-10 in the aqueous phase were 1wt%, and the weight percentage of sodium alginate was 0.9wt%. Rapeseed oil was added to the dispersed phase with an oil-water ratio of 3:7, and an emulsion was prepared using an ultra-high pressure homogenizer (SCIENTZ-207A, Xinzhi, Ningbo, China) at a homogenization pressure of 80 MPa.

[0067] The microstructure of the emulsion was observed using an optical microscope. A proper amount of the emulsion was taken with a pipette and placed on a glass slide and observed at 40 times. When initially prepared, the droplets of the emulsion based on LNP-7.5 had the smallest size. The droplets of the emulsions made from untreated lignin, LNP-5, and LNP-10 began to show obvious flocculation and aggregation on the third day of storage, and large droplets with obvious low transmittance appeared. However, the droplets of the emulsion made from LNP-7.5 did not become significantly larger on the seventh day ( Figure 7 ).

[0068] 7. Determination of the in vitro antioxidant properties of lignin-based Pickering emulsions loaded with curcumin (Cur)

[0069] Curcumin was dissolved in the LPE-7.5 emulsion prepared in Example 1 to prepare a curcumin-loaded Pickering emulsion having a curcumin concentration of 1 mg / mL.

[0070] (1) DPPH free radical scavenging experiment: First, 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) was dissolved in ethanol to a concentration of 0.1 mM. A Pickering emulsion loaded with curcumin at a curcumin concentration of 1 mg / mL, a free curcumin solution at a curcumin concentration of 1 mg / mL, and a blank LPE-7.5 emulsion without curcumin were diluted 200, 100, 50, 20, 10, and 5 times, respectively, to obtain curcumin emulsions and free curcumin solutions with curcumin concentrations of 5, 10, 20, 50, 100, and 200 μg / mL, respectively, and blank emulsion samples with corresponding dilution multiples. 0.5 mL of the samples of different concentrations were dissolved in 2 mL of DPPH solution, vortexed at high speed to mix evenly, and then the mixed solution was allowed to stand at room temperature for 30 min in a dark place. The absorbance of each sample was measured at 517 nm using a UV-visible spectrophotometer. The DPPH scavenging ability (AAD) was calculated using the following formula:

[0071] AAD(%)=(Ac-(As-Ab)) / Ac×100

[0072] Where: Ac is the absorbance of the control, A s The sample solution (V DPPH乳液 :V 样品溶液 =1:1) after the absorbance, A b The sample solution (V 乙醇 :V 样品溶液 =1:1) after the absorbance.

[0073] DPPH is widely used to evaluate the antioxidant capacity of nutritional supplements in transferring unstable H atoms to free radicals. Its methanol or ethanol solution is dark purple and has a maximum absorption peak at around 517nm. Figure 8 As shown in the middle panel A, the DPPH scavenging ability of all samples increases with the decrease of the dilution factor. When the sample dilution factor is 5, that is, the curcumin concentration is 200μg / mL, the DPPH scavenging rate of the free curcumin solution is only 29.20%, while the DPPH scavenging ability of the lignin-based Pickering emulsion loaded with curcumin is significantly increased to 63.45%. This is attributed to the excellent water dispersibility and large specific surface area of ​​the Pickering emulsion, which promote the interaction between curcumin and free radicals. In addition, the lignin-based Pickering emulsion itself also has a certain DPPH scavenging ability, and the results show that the two may have a synergistic effect.

[0074] (2) ABTS+· free radical scavenging experiment: 7 mM ABTS+· solution and 7.35 mM K 2 S 2 O 8 The solutions were mixed in a volume ratio of 1:2 and then placed in a dark environment at room temperature for 12-16 hours. The ABTS+· dilution was diluted with anhydrous ethanol before use so that the absorbance of the ABTS+· dilution at 734 nm was 0.70±0.02 before subsequent experiments.

[0075] The preparation of the corresponding samples was the same as that of the DPPH·free radical scavenging experiment.

[0076] Add 0.5 mL of ABTS+· diluent and 1.5 mL of the sample to be tested to the centrifuge tube and vortex at high speed to mix thoroughly. After reacting at room temperature in the dark for 5 minutes, measure the absorbance at 734 nm. Use the following formula to calculate the ABTS+· scavenging ability (AAA):

[0077] AAA(%)=(Ac-As) / Ac×100

[0078] Where Ac is the absorbance of the control (without test sample) and As is the absorbance of the sample (with test sample).

[0079] The ability of curcumin to scavenge ABTS+ free radicals mainly comes from the phenolic hydroxyl group and α,β-unsaturated diketone structure in its structure. Figure 8 As shown in the middle panel B, the ABTS+· scavenging ability of all samples increases with the decrease of the dilution factor of the concentration sample. When the curcumin aqueous solution was diluted 5 times, that is, when the curcumin concentration was 200μg / mL, the ABTS+· scavenging rate of free curcumin was 65.31%; the ABTS+· scavenging rate of the blank lignin-based Pickering emulsion at the corresponding dilution factor was about 45.39%; and the ABTS+· scavenging rate of the lignin-based Pickering emulsion loaded with curcumin was significantly improved to 94.03% when the dilution factor was 5, that is, when the curcumin concentration was 200μg / mL. This is because the lignin-based Pickering emulsion itself also has a certain ABTS+· scavenging ability. The combination of curcumin and the emulsion prevents the formation of curcumin aggregates, improves the physicochemical stability of curcumin, protects its biological activity, and the results show that the two may have a synergistic effect.

[0080] 8. Cell activity experiment of curcumin-loaded lignin-based Pickering emulsion.

[0081] The cytotoxicity of nanoparticles is one of the important parameters for evaluating the biosafety of nanoparticles during their application. Caco-2 cells are human cloned colorectal adenocarcinoma cells that are similar to differentiated intestinal epithelial cells in structure and function. They are often used to simulate in vivo intestinal cell proliferation and toxicity tests to evaluate the effects of nano-delivery vectors on cell viability. Caco-2 cells were cultured at 37°C and 5% CO 2 , humidity is 95% in an incubator. DMEM cell culture medium is used, and contains 10% fetal bovine serum and 1% penicillin-streptomycin (100 IU / mL penicillin, 100 μg / mL streptomycin). First, it is necessary to determine the cell inoculum added to each well of the 96-well plate, measure the cell viability under different cell inoculums, and select the appropriate cell inoculum. Different concentrations of free curcumin or curcumin-loaded emulsions (this test uses the LPE-7.5 emulsion prepared in Example 1) are added to the culture plate to determine the level of protection for the cells. After the treatment is completed, CCK-8 reagent is added to each well to ensure that the volume ratio of CCK-8 reagent to cell culture medium is 1: 10, and then the 96-well plate is placed in an incubator (37 ° C) for incubation for 1-2 hours, and the absorbance at 450 nm is measured using an enzyme reader to determine the cell viability of different treatment groups.

[0082] Results Fig. 9When the curcumin concentration was lower than 200 μg / mL, there was no significant difference in cell viability between the free curcumin treatment group and the curcumin-loaded Pickering emulsion treatment group. However, as the curcumin concentration increased to 300 μg / mL, the cell viability of the free curcumin group decreased significantly, while the toxicity of the curcumin-loaded lignin-based Pickering emulsion was less than that of the free curcumin treatment group. This may be due to the protective effect of lignin-based Pickering on Caco-2 cells. The results showed that the curcumin-loaded lignin-based Pickering emulsion had no significant cytotoxicity when the curcumin concentration was lower than 300 μg / mL, and had better biocompatibility.

[0083] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A method for preparing a lignin-based Pickering emulsion, characterized in that: The steps include: 1) preparing a low eutectic solvent, adding water, cooling and setting aside; 2) dissolving lignin in a low eutectic solvent, standing, and centrifuging to obtain a lignin solution; 3) diluting the lignin solution dropwise with deionized water, dialyzing, and freeze-drying to obtain lignin nanoparticles; 4) dissolving lignin nanoparticles and sodium alginate in an aqueous phase, mixing the aqueous phase and the oil phase, and homogenizing under ultrahigh pressure to obtain a lignin-based Pickering emulsion.

2. The method for preparing a lignin-based Pickering emulsion according to claim 1, characterized in that: In step 1), the preparation method of the low eutectic solvent is: betaine and lactic acid are mixed in a molar ratio of 1:1.5 to 2.5, and heated in a water bath at 80 to 95° C. until they are completely dissolved, thereby forming a low eutectic solvent.

3. The method for preparing a lignin-based Pickering emulsion according to claim 1, characterized in that: In step 2), the dissolution process is carried out at 20-30° C., the dissolution process is assisted by magnetic stirring, the stirring speed is 600-800 rpm, the standing time is 10-14 hours, and the lignin concentration in the obtained lignin solution is 7-10 mg / mL.

4. The method for preparing a lignin-based Pickering emulsion according to claim 1, characterized in that: In step 3), the dilution process is assisted by magnetic stirring, the stirring speed is 600-800 rpm, the dropping rate of deionized water is 1 mL / min, and the final weight percentage of the added deionized water is 50 wt%.

5. The method for preparing a lignin-based Pickering emulsion according to claim 1, characterized in that: In step 4), the weight percentage of lignin nanoparticles in the aqueous phase is 0.5-1 wt%, and the weight percentage of sodium alginate is 0.6-0.9 wt%.

6. The method for preparing a lignin-based Pickering emulsion according to claim 1, characterized in that: In step 4), the volume ratio of the oil phase to the water phase is 1:9 to 9:

1.

7. The method for preparing a lignin-based Pickering emulsion according to claim 1, characterized in that: The oil phase is one of rapeseed oil, soybean oil, olive oil and linseed oil.

8. The method for preparing a lignin-based Pickering emulsion according to claim 3, characterized in that: In step 2), the concentration of lignin in the obtained lignin solution is 7.5 mg / mL.

9. The method for preparing a lignin-based Pickering emulsion according to claim 5, characterized in that: In step 4), the weight percentage of lignin nanoparticles in the water phase is 1 wt%, the weight percentage of sodium alginate is 0.9 wt%, and the volume ratio of the oil phase to the water phase is 3:

7.

10. A lignin-based Pickering emulsion, characterized in that The invention is prepared based on the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for efficiently separating all components of wood fiber

    CN111826986A

  • Preparation method of multifunctional natural lignin-based Pickering emulsion

    CN114601740A

  • Starch nanocrystal-sodium alginate composite particle stable Pickering emulsion and preparation method thereof

    CN116178798A

  • Eucommia ulmoides leaf degumming micro-powder matcha Pickering emulsion as well as preparation method and application thereof

    CN116874817A

  • Full-biomass sodium alginate / lignin water-retaining slow-release hydrogel as well as preparation method and application thereof

    CN117624647A